Knowledge and behavior of Indonesian general practitioners on cervical cancer early detection - Laila Nuranna; Nessyah Fatahan; Alfu Nikmatul Laily; Gatot Purwoto (Universitas Airlangga, 2020)
Objective: Outline the correlation between cervical cancer-related knowledge and voluntary enrollment on early detection of cervical cancer.Material and Methods: Cross sectional design was performed. The inclusion is general practitioner women which currently married. Knowledge and behavior were assessed using questionnaire.Results: Among 367 respondents who filled the questionnaire, 77.4% of them (284) satisfy the inclusion criteria. 56% has high knowledge, and 42.3% has adequate knowledge. Moreover, 62.7% subjects ever performed cervical cancer early detection to themselves; 39.8% with VIA (visual inspection with acetic acid) and 46.5% with Papsmear and/or HPV DNA. Proportion of no early detection history with low and adequate knowledge 1.9 and 1.5 times simultaneously higher than proportion of no early detection with high knowledge. There is no significant correlation between level of knowledge and early detection history.Conclusion: There was no significant correlation between the level of knowlegde and voluntary enrollment for early detection of cervical cancer for general practitioners in Indonesia.